PROSES PRODUKSI PART SHAFT MIXER VERTICAL MENGGUNAKAN MESIN BUBUT KONVENSIONAL DAN MESIN MILLING CNC - Adiyanto Pratama, Sandy; Koswara, Engkos (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
PT. Amanah Jaya Persada is a company engaged in the manufacture of automotive parts, precision parts, jigs & fixtures, molds & dies, casting parts, fabrication and manufacture of tools for other industrial needs. PT. Amanah Jaya Persada manufactures Vertical Shaft Mixer Parts using conventional lathes and CNC Milling machines. In the process of making Part Shaft, the process of measuring the initial diameter of the material, making a sketch of the size of the workpiece, and the process of making the CNC Milling program code. The purpose of this research is to find out the production process time for Vertical Shaft Mixer Parts on Conventional Lathes and CNC Milling Machines, to understand the types of program codes on CNC milling machines. The research stages were carried out from the observation stage, problem formulation, literature study, field practice, data collection and data analysis, followed by material specifications, Conventional Lathes and CNC Milling Machines. The results showed that the production process for the Part Shaft Mixer Vertical using a conventional lathe required machining time of 33 minutes 6 seconds, while for a CNC milling machine it took 14 minutes 6 seconds. The CNC milling process uses a combination of G91 incremental and absolute G90 machining commands, G28 to return to the reference point for repeated feeding, as well as M code for rotating spindle commands, changing tools, turning on the coolant and stopping the machine / program is complete.